Analysis of Obstacles and Difficulties in the Process of Implementing Learning for Students Based on the Learning Management System (LMS) - Mesta Mesta Limbong (Universitas Ahmad Dahlan, 2023)
Indonesia is among the world's largest archipelagic regions, with thousands of tiny islands. So many people may not obtain a decent education, such as attending advanced learning. To conquer this circumstance, particularly in light of the unreleased impact of COVID-19 and the global scale crisis, which undoubtedly impacts education in general. Each method for adjusting to shifts in higher education employs a Learning Management System (LMS). This descriptive study uses secondary data and a phenomenological approach to analyze how lecturers prepare lecture material using LMS. This study approach indicates that not all lecturers have scheduled material that students can download at any time via LMS. Because it is necessary to prepare lecturers and support structures that can be easily accessed per applicable regulations to organize the LMS, efforts that can be made to overcome obstacles to the LMS implementation include requiring each lecturer to prepare lecture materials in a structured and timely manner, as well as monitoring. Students can then repeat material that they might have already missed. This is one ideal solution for shutting the achievement gap.